Tropical-infection-precipitated acute-on-chronic liver failure: a distinct, lower-mortality phenotype in a Northeast Indian cohort - Saravanamuthu, Ponn Karthikeyan; Das, Anup Kumar; Rajkakati, Rashmi; Sonowal, Aparna (International Journal of Research in Medical Sciences, 2026)
Background: Leptospirosis and scrub typhus are endemic tropical infections in northeast India capable of precipitating acute-on-chronic liver failure (ACLF). Both are doxycycline-responsive. Whether tropical-precipitated ACLF represents a distinct, lower-mortality phenotype amenable to targeted therapy is unknown. Methods: Seventy consecutive adults with EASL-CLIF ACLF were prospectively enrolled at a tertiary teaching hospital in Northeast India (October 2024-September 2025). Leptospirosis was diagnosed by IgM ELISA and/or compatible clinical syndrome; scrub typhus by Orientia tsutsugamushi IgM ELISA or Weil-Felix titre ≥1:160. All clinically suspected tropical infections received empirical doxycycline 100 mg twice daily alongside standard broad-spectrum antibiotics. Tropical-precipitated versus non-tropical-precipitated subgroups were compared for severity, inflammatory markers, and 28-day mortality. Results: Tropical infection precipitated 17 of 70 ACLF episodes (24.3%)- 10 leptospirosis (14.3%), 6 scrub typhus (8.6%), and 1 mixed Leptospira-Orientia infection (1.4%). The tropical subgroup had a higher proportion of grade 1 ACLF (41.2% versus 7.5%; p=0.003), lower admission PCT (2.54 versus 6.73 ng/ml), and significantly higher admission creatinine (5.91 versus 3.19 mg/dl; p=0.018). Twenty-eight-day mortality was 35.3% in the tropical subgroup versus 62.3% in non-tropical patients (OR 0.33; 95% CI 0.11-1.05; p=0.091). Compared with alcohol-precipitated ACLF specifically, tropical-precipitated mortality was significantly lower (35.3% versus 73.9%; OR 0.19, p=0.024). Conclusions: Tropical-infection-precipitated ACLF is a distinct phenotype with lower presentation severity and a clinically important mortality advantage over alcohol-precipitated ACLF. Empirical doxycycline in ACLF patients with suspected leptospirosis or scrub typhus in endemic regions deserves routine inclusion in management protocols.